Islamic banking in Malaysia: a study of attitudinal differences of Malaysian customers - Haque, A. K. M. Ahasanul (EuroJournals, Inc., 2010)
This research emphasizes attitudinal difference of Malaysian customers about Islamic banking services. The banking service providers can gain excellent benefit from Islamic banking practices upon identification of these differences. A structured questionnaire was constructed to collect the necessary data to answer the research questions as being framed on related affective factors of attitudinal differences of consumers’ in Malaysia. In this research we have employed independent sample ‘t’ test and ANOVA to test the hypotheses. Results showed that Malaysian consumers have positive attitude toward Islamic banking. Results of ‘t’ test showed significant attitudinal differences between males and females. In addition, the results of ANOVA showed significant attitudinal difference existed only between Malay and Chinese and between Chinese and Indian, while the overall attitudes of all three races were positive toward Islamic banking. One potential limitation of this study was the size and composition of the group which participated in the study. Therefore, a generalization about the entire population of Malaysian banking customers of banking sector is inappropriate. In addition, this research could not incorporate all levels of diverse attributes of Islamic banking that might influence customers’ behavior. The results of this study can facilitate the Islamic banking service providers to introduce new, innovative service offerings based on attitudinal differences and of course, in accordance with Islamic rules and regulation.